Vol 1 - "Khan, Shakil Ahmad" (New Delhi, 2017)
This encyclopedic essential reference work covers over 75, 000 entries containing all statutory and judicial definitions of key standard legal words, maxims and phrases ? The work also includes: - Entries from emerging areas of law covering Information Technology, Cyber Law, Alternative Dispute Resolution, Intellectual Property Rights and International Trade and Commerce - Terms from specialized areas such as commerce, stock exchange, forensic medicine, mercantile, maritime and military law - Numerous special terms governing customs, which are prevalent in many parts of India - Words peculiar to Hindu Law, Muslim Law and the other personal laws - Words, phrases and expressions which are peculiar to English Statutes, decisions and treatises that have made their entry in Indian legal literature - Words defined in standard legal text books such as the works of Justice Story, Blackstone, Williams and Russell have been adopted under appropriate entries - Also includes a collection of Latin terms, Legal Maxims, Historical/Archival words, definitions from standard legal textbooks, European legal terms and Indian regional terms ? Approximately 6000 new definitions covering Supreme Court and High Court judgments as well as Central Acts, Rules, Regulations, Guidelines, Notifications and Circulars have been added in the revised edition. ? Widely cited in Supreme Court and High Court Judgments ? All latest Central Acts, Rules, Regulations, Guidelines, Notifications and Circulars have been exhaustively covered ? The existing definitions have been replenished by adding citations of recent judgments which have reiterated the existing definitions
Keywords: Law